Burnout among Physicians: Prevalence, Contributing Factors and Solutions: A Review of Literature - Magdalena Grotowska; Martyna Łukasiewicz; Aleksandra Strawińska; Maria Wydro (Quality in Sport)
The state of burnout is a nuanced condition primarily connected to enduring occupational stress, defined by emotional drain, disconnection from others, and a lesser feeling of personal competence. Identified by the World Health Organization as a critical concern within workplace, burnout is particularly widespread among healthcare professionals, attributed to rigorous workloads, bureaucratic obstacles, and inadequate support systems. This paper examines the underlying factors contributing to burnout- occupational, institutional, and individual aspects, and highlights the consequences for both healthcare providers and patient care. The analysis suggests that burnout adversely impacts both the psychological and physical health of medical workers and reduces the quality of patient care, consequently heightening systemic inefficiencies in the healthcare system. Furthermore, this research intends to delve into various individual, organizational, and systemic methods crafted to mitigate burnout, stressing the need for integrated interventions that cultivate resilience and advance well-being for healthcare practitioners. By examining the intricate aspects of burnout, this study aspires to impact policy and practice, consequently improving the standard of care and cultivating a healthier work environment in medical sector.